2019
DOI: 10.1111/ijd.14567
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of autologous adipose‐derived stem cells vs. fractional carbon dioxide laser in the treatment of post acne scars: a split‐face study

Abstract: Background Scarring is a distressing outcome of acne, as it causes cosmetic and psychological problems to the patients. Unfortunately no single treatment is satisfactory; instead, employing multiple modalities may have better outcome. Autologous adipose tissue‐derived adult stem cells (AT‐ASCs) and their secretory factors can stimulate collagen synthesis; angiogenesis and migration of fibroblasts thus regenerate damaged tissues. Also, conventional treatments for acne scarring, such as lasers and topical regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 37 publications
2
41
0
Order By: Relevance
“…One study used the CO 2 laser pinpoint irradiation technique, which is an effective treatment for atrophic acne scars as fractional photothermolysis, 17 so it could be incorporated into further studies. Thus, a total of 8 studies meeting the inclusion criteria were included in this research, and all the studies are presented in Figure 2 18‐25 . The characteristics of each study are summarized in the following tables (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…One study used the CO 2 laser pinpoint irradiation technique, which is an effective treatment for atrophic acne scars as fractional photothermolysis, 17 so it could be incorporated into further studies. Thus, a total of 8 studies meeting the inclusion criteria were included in this research, and all the studies are presented in Figure 2 18‐25 . The characteristics of each study are summarized in the following tables (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…In consistence with the idea of our study, Abou Eitta et al 31 included 10 adult patients with postacne scars on both sides of the face in a split face comparative study. One side received autologous adipose tissue‐derived adult stem cells (AT‐ASCs) single injection while the other received three sessions of the fractional CO 2 laser.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these concerns, autologous fat grafting has been shown to be as effective at treating acne scarring as established techniques such as fractional carbon dioxide laser (FxCR). It was shown that just one treatment using autologous adipose tissue‐derived adult stem cells provided significant global improvement when compared to three treatments involving FxCR over a 3‐month period 70 …”
Section: Soft Tissue Regenerationmentioning
confidence: 99%